Biomechanical comparison of three tibial tunnel positions for PCL reconstruction: a 3D finite element analysis - Siman Tian; Yi Zheng; Yubin Long; Yingzhen Niu; Zhikuan Li; Jiangtao Dong (BMC Musculoskeletal Disorders)
Abstract Purpose To compare the biomechanical properties of the graft during PCL reconstruction by three-dimensional finite element analysis of the PCL trans-tibial reconstruction technique with three different tibial bony channel exit positioning points, to determine which method of positioning is better able to avoid wear and tear between the graft and bony channel, and to reduce the failure rate of the PCL reconstruction. Methods This is a study limited to computational simulation and based on data from a single anatomical model. Thirty-year-old male volunteers were selected. A three-dimensional knee joint model consisting of the distal femur, the proximal tibiofibula and the posterior cruciate ligament was established based on CT scanning and three-dimensional reconstruction of the left knee joint. According to the different positioning points of the tibial tunnel exit, the PCL model of tibial side PCL anatomical region center point reconstruction, the PCL model of Fanelli suggested point (i.e., 10 mm below and 5 mm lateral to the PCL anatomical point) reconstruction, and the PCL model of tibial side posterior posterior joint capsule distal anticompromise and posterior mediastinum reference positioning point (i.e., 5 mm above the posterior capsule distal retropubic, 5 mm medial to the posterior mediastinum) reconstruction were established (respectively designated as Model 1, Model 2, and Model 3). The diameter of the entire graft was set uniformly at 7 mm. With the knee flexed at 90° and the midpoint of the line connecting the medial and lateral apexes of the tibial intercondylar ridge as the reference point, a standardized backward thrust displacement of 5 mm was applied to simulate a posterior knee drawer test with all proximal femoral degrees of freedom constrained. The model overall Mises stress, tibial plateau Mises stress, PCL Mises stress, PCL contact Cpress stress, PCL contact stress and PCL contact effective area were measured. Results Simulated posterior drawer tests demonstrated that Model 3 exhibited a substantial reduction in PCL contact Cpress stress (22.57 MPa) compared to Model 1 (32.93 MPa) and Model 2 (29.86 MPa). Additionally, the ratio of contact force (277.48 N) to effective graft-tibial contact area (50.19 mm²), representing the contact force per unit area, was also the lowest in Model 3 compared to Model 1 (213.88 N/17.65 mm²) and Model 2 (470.77 N/63.75 mm²). These findings indicate that Model 3 significantly reduced frictional loads between the graft and tibia, highlighting its biomechanical optimization potential. Further analysis revealed that Model 3 also displayed the lowest tibial plateau Mises stress (48.80 MPa). However, its PCL tensile stress (69.71 MPa) was significantly higher than that of Model 1 (41.03 MPa) and Model 2 (40.90 MPa), suggesting that while Model 3 minimizes friction dependency, it primarily transfers loads through graft tension. Conclusion Compared with the anatomic regional center point and Fanelli point reconstruction PCL, the grafts of the soft tissue reference tibial localization reconstruction PCL method were subjected to greater tensile forces, but they had significantly lower friction with the tibia and were able to reduce contact wear with the tibia. This can enhance long-term patient outcomes. Our study offers crucial biomechanical evidence for optimizing tunnel positioning in PCL reconstruction, propelling the advancement of surgical techniques.